2012
DOI: 10.3390/ijms131012573
|View full text |Cite
|
Sign up to set email alerts
|

Short Hairpin RNA (shRNA) Ether à go-go 1 (Eag1) Inhibition of Human Osteosarcoma Angiogenesis via VEGF/PI3K/AKT Signaling

Abstract: Ether à go-go 1 (Eag1) channel is overexpressed in a variety of cancers but the therapeutic potential of Eag1 in osteosarcoma remains elusive. In this study, we constructed an Ad5-Eag1-shRNA vector and evaluated its efficiency for Eag1 knockdown and its effects on osteosarcoma. Our results showed that Ad5-Eag1-shRNA had high interference efficiency of Eag1 expression and suppressed osteosarcoma growth both in vitro and in vivo. To explore the molecular mechanism underlying tumor growth inhibition induced by Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…A number of studies reported that VM existed in various tumors including ovarian cancer [5,6,7,8]. There is an intimate link between VM and tumor and this connection could enhance tumor growth and metastasis by providing an adequate vascular supply [9].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies reported that VM existed in various tumors including ovarian cancer [5,6,7,8]. There is an intimate link between VM and tumor and this connection could enhance tumor growth and metastasis by providing an adequate vascular supply [9].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al found that increased expression of miR-126 enhanced the sensitivity of NSCLC cells to chemotherapy agents through negative regulation of the VEGF/PI3K/Akt/MRP1 signaling pathway [32]. Results from another study suggest that Eag1 siRNA could inhibit tumor growth and angiogenesis in osteosarcoma through modulating the activation of VEGF/PI3K/AKT signaling [33]. Similar to their results, we found the protein levels of VEGFA were up-regulated in osteosarcoma tissues and in the osteosarcoma cell line SAOS-2 compared with adjacent nontumorous osteosarcoma tissues and normal human osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several meta-analysis have shown that increased VEGF levels in patients are directly related to decreased survival and to tumour progression and consequently, to a poor prognosis [38,39,40] . Studies that have investigated molecular mechanisms involving VEGF showed the importance of regulating the VEGF/PI3K/AKT signalling pathway in the progression and development of osteosarcoma [41,42] .…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%